EVOLUTIVE PECULIARITIES OF AN ILEO-CECAL VALVE TUMOR: CASE REPORT - Elena Neștian (Journal of Surgical Sciences, 2019)
Introduction: Tumors of ileo-caecal valve are most clinically manifested either through transit disorders or anemic syndrome.